Do childhood callous-unemotional traits drive change in parenting practices? - Hawes, D.; Dadds, M.; Frost, A.; Hasking, Penelope (Lawrence Erlbaum Associates, Inc., 2011)
This study examined the relationship between callous-unemotional (CU) traits and parenting practices over time in a mixed-sex community cohort (N=1,008; 52.6% boys), aged 3 to 10 years (M=6.5, SD=1.3). Measures of CU traits, externalizing psychopathology, parenting practices, and socioeconomic risk factors were collected at baseline, and parenting practices and CU traits were reassessed at 12-month follow-up. CU traits uniquely accounted for change in three domains of parenting (inconsistent discipline, punishment, and parental involvement). Likewise, multiple domains of parenting (positive parenting, parental involvement, and poor monitoring/supervision) uniquely predicted change in CU traits. These seemingly bidirectional dynamics between CU traits and parenting were found to be largely moderated by child age and sex. Results partially replicate previous findings regarding the association between quality of parenting and prospective change in CU traits, and provide initial evidence that CU traits disrupt parenting practices over time.